Travessias em educação e saúde: processos educativos em gênero e sexualidades - Silva, Luciene Aparecida (2014)
The present research problematizes experiences in health and education, focusing on the themes of gender and sexuality, which were experienced during the years from 2011 to 2013 by users of an anti-manicomial institution in the countryside of Minas Gerais, Brazil. For such, I present the contexts in which the educative processes happened, also systemizing the cultural texts, which are poems, music and theatrical plays, constructed in the dialogs denominated in the present research as narratives-poems. Some of these dialogs were digitalized and exposed on a panel at the entrance of the institution, a wall blog; after the expositions, they were archived and might be research sources, although they were not constructed with such objective. Such productions put into motion from the readings of the book Vintém de cobre, written by Cora Coralina, of the tale O Alienista, by Machado de Assis and of an activity denominated Time Line, using music to review memories, allowed dialogs on experiences of resistance from subjects that construct what I denominate lives-poems. In this context, they name the coexistence spaces as ―school‖, which I analyze contemplating the Foucaultian concept of Heterotopia. They are other educative spaces that occurred at the city square, at the club, in the institution‘s garden, between such. Therefore, I consider the texts produced as cultural artifacts that allow deconstructions of excluding learning on the themes of gender, sexuality and madness. The investigative crossings occurred when I reviewed and systematized the texts, challenging myself in this rereading to ―listen‖ once more to the narratives. In this trajectory, I identified the workshop spaces as places of liberty, in which the texts produced show the taste for poetry, the admiration for school and education, and, especially, the learning of sexuality and gender. As they unraveled the production of cultural artifacts, the denominated narrative poems from the reading of the book Vintém de cobre: meias confissões de Aninha by Cora Coralina, a CD with the Time Line music, a conjunction of circumstances that, while narrating the histories experienced, allowed to remember other times and the treatments given to madness; two theater plays, one based on the tale O Alienista by Machado de Assis, the other a rewriting of a ―bumpkin‖ marriage, which instigated dialogs on the differences. I consider the subjects of the experiences as narrators of stories experienced and narrators of methodologies that can instigate the reflection on normality standards.